The Relationship of Varied Learning Methods with the Learning Activeness of Automotive Training Participants at the Painan Vocational Training Center - Arief Fransisko; Jamaris Jamaris (Universitas Negeri Padang, 2022)
This research was motivated by the trainees who were active during the automotive training at BLK Painan. This study aims to see an overview of the learning methods used by automotive training instructors when providing training materials, to see a description of the learning activities of automotive trainees, and to see the relationship between varied learning methods and the learning activities of automotive trainees at BLK Painan. This type of research is quantitative with a correlational approach. The population of this research is the automotive training participants in the 2021 period as many as 32 people. While the sample was taken using the saturated sample technique. Data collection techniques using a questionnaire. As for the data analysis technique, the percentage formula and the product moment formula are used. The results of this study indicate that (a) the instructor has applied various learning methods well, namely by applying three forms of methods, the lecture method, the discussion method, and the practical method; (b) the trainees already have a good activity at the time of participating in the training; and (c) there is a significant relationship between the various learning methods and the active learning of automotive training participants at BLK Painan.Keywords: study, study methods, learning actvity